Implementation of Customer Data Protection and Transaction Data in Using Mobile Banking (Case Study of PT Bank Central Asia, Tbk) - Sitorus, Rolib; Wijaya, Marcelia (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the responsibility of banking institutions and the government in terms of legal protection for customers who use mobile banking services. Empirical normative research methods were used by the author in this research. This means evaluating the implementation of normative legal provisions (legislation) and is linked to field data obtained from interviews with subjects relevant to the research problem. The research data collection method is carried out through field studies (field research) and library research, namely conducting research by studying in the library through reading references in the form of books, articles and legal journals as well as through the results of interviews which are then used as material to produce conclusions that answer research problems. However, the data analysis used is qualitative data analysis, which means collecting, analyzing and interpreting primary and secondary data that is arranged systematically, clearly and in detail. Next, legal thinking logic is used to analyze this data. The research results show that the responsibility of banks and government institutions for losses experienced by customers should ideally be linked to proof that the losses originate from errors or negligence by the customer or the bank.